A novel IBA57 variant is associated with mitochondrial iron–sulfur protein deficiency and necrotizing myelopathy in dogs - Mandigers, Paul J. J.; Stehling, Oliver; Vos-Loohuis, Manon; Van Steenbeek, Frank G.; Lill, Roland; Leegwater, Peter A. (Frontiers in Genetics, 2023)
Introduction: Hereditary necrotizing myelopathy (HNM) in young Kooiker dogs is characterized by progressive ataxia and paralysis with autosomal recessive inheritance. The basic genetic defect is unknown. We investigated the possible cause by a genome-wide analysis using six affected and 17 unrelated unaffected Kooiker dogs and by functional follow-up studies.The HNM locus was mapped by a case-control study using a dense SNP array and confirmed by linkage analysis of two pedigrees. The gene exons in the critical region were analyzed by next generation sequencing. The functional effect of the candidate canine IBA57 pathogenic variant was biochemically examined in an established HeLa cell culture model in which the endogenous IBA75 gene product was depleted by RNAi.The basic defect was localized in the centromeric 5 Mb region of canine chromosome 14. The most associated SNP co-segregated fully with HNM and reached a LOD score of 6.1. A candidate pathogenic mutation was found in the iron-sulfur cluster assembly gene IBA57 and led to the amino acid substitution R147W. Expression of human IBA57 harboring the canine R147W exchange could only partially restore the biochemical defects of several mitochondrial [4Fe-4S] proteins upon IBA57 depletion showing that the mutant protein is functionally impaired.Discussion: Pathogenic variants in human IBA57 cause multiple mitochondrial dysfunction syndrome 3 (MMDS3), a neurodegenerative disorder with distant similarities to HNM. The incomplete functional complementation of IBA57-depleted human cells by IBA57-R147W identifies the DNA mutation in affected Kooiker dogs as the genetic cause of HNM. Our findings further expand the phenotypic spectrum of pathogenic IBA57 variants.